Rare Co-occurrence of Ocular Myasthenia Gravis and Thyroid-Associated Orbitopathy (Ophthalmopathy) in an Individual With Hypothyroidism - An, Ran; Li, Yan; Yang, Baiyuan; Wang, Hui; Xu, Yanming (Frontiers in Endocrinology, 2019)
Ocular myasthenia gravis (Ocular MG, OMG) shares many clinical features with thyroid-associated orbitopathy or thyroid-associated ophthalmopathy (TAO). In the rare instance of their coexistence, clinicians may fail to diagnose ocular MG when TAO is also present. Here we report the case of a patient with both TAO and ocular MG, whose “hyperthyroidism”—most likely the hashitoxicosis variant of Hashimoto's thyroiditis—rapidly transformed to hypothyroidism after radioactive iodine therapy. This is reminiscent of a previous case of a patient with MG, in whom disease onset coincided with the methimazole-induced transformation from hyper- to hypothyroidism. It is possible that the same transformation from “hyper-” to hypothyroidism, which occurred after radioactive iodine therapy and was accompanied by hypothyroidism-associated orbitopathy (ophthalmopathy), may have induced the development of myasthenia gravis in our patient. The hypothyroidism may have been caused by the radioactive iodine therapy and/or it may simply reflect the natural course of the hashitoxicosis variant of Hashimoto's thyroiditis. The co-occurrence of hypothyroidism, hypothyroidism-associated orbitopathy (ophthalmopathy) and ocular MG has never been reported. Our case highlights the need for clinicians to focus on overlapping symptoms of hyperthyroidism and the hashitoxicosis variant of Hashimoto's thyroiditis, and to carefully differentiate between them, especially when deciding on radioactive iodine therapy. In addition, our case highlights that the possible co-occurrence of TAO should be considered when a patient with thyroid disease displays both ptosis and eye movement dysfunction, and when only the ptosis is dramatically resolved after treatment with pyridostigmine bromide.